If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -8 = x + 47 Reorder the terms: -8 + 6x = x + 47 Reorder the terms: -8 + 6x = 47 + x Solving -8 + 6x = 47 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -8 + 6x + -1x = 47 + x + -1x Combine like terms: 6x + -1x = 5x -8 + 5x = 47 + x + -1x Combine like terms: x + -1x = 0 -8 + 5x = 47 + 0 -8 + 5x = 47 Add '8' to each side of the equation. -8 + 8 + 5x = 47 + 8 Combine like terms: -8 + 8 = 0 0 + 5x = 47 + 8 5x = 47 + 8 Combine like terms: 47 + 8 = 55 5x = 55 Divide each side by '5'. x = 11 Simplifying x = 11
| 6c+21=17c+10 | | 5x+6=3x+8+2x-7 | | 5x+5=3x+8+2x-7 | | 4a+5=15 | | 18a+3= | | 0.5y^3=13.5 | | 56=-13 | | 15x-20=70 | | X+4=28-x | | x(3x-15)=0 | | -7x+5=-x-1 | | 5-0.8(d-18)=0.4(12d-18) | | 3-3x=x+47 | | 81x^2=126x-49 | | (x+9)(x-1)= | | 2x+7=-3+5x | | 5x+15=3x+8+2x-7 | | 3y-13+2y-12=180 | | 2t-83+2t-51=180 | | 14y-6=5 | | 5x-2=-x-32 | | -3r+20=15r-8 | | 11x+11+9x-11=180 | | 2t-51+2t-83=180 | | 11x+11+2y-12=180 | | 6x-7=53-4x | | 8x+4y=52 | | 2x+7=8(4+x) | | 2q-88+q+58=180 | | 2x+7=8(4+6) | | 0.3(n+4)=5 | | 90=6x-1 |